The future of African customary law - Fenrich, Jeanmarie; Galizzi, Paolo; Higgins, Tracy E. (Cambridge University Press, 2011)
"Customary laws and traditional institutions in Africa constitute comprehensive legal systems that regulate the entire spectrum of activities from birth to death. Once the sole source of law, customary rules now exist in the context of pluralist legal systems with competing bodies of domestic constitutional law, statutory law, common law, and international human rights treaties. The Future of African Customary Law is intended to promote discussion and understanding of customary law and to explore its continued relevance in sub-Saharan Africa. This volume considers the characteristics of customary law and efforts to ascertain and codify customary law, and how this body of law differs in content, form, and status from legislation and common law. It also addresses a number of substantive areas of customary law including the role and power of traditional authorities; customary criminal law; customary land tenure, property rights, and intestate succession; and the relationship between customary law, human rights, and gender equality"--